Methylene Blue and Iron (II) Adsorption onto Raphia Hookeri Seed: A Comparative Equilibrium Isotherm Study - Tarbuka, P. F; Gumus, R. H (International Journal of Chemical and Process Engineering Research, 2021)
In this study, activated carbon prepared from Raphia hookeri seed was employed as an adsorbent to take up methylene blue (an organic ion-in-solution) and iron (II), a metal ion-in-solution. The biosorbent was prepared using chemical activation using sodium hydroxide (NaOH) as an impregnating agent. Calibration was performed with a focus on the change in the adsorbate concentration. The equilibrium isotherms study was conducted by considering a range of sorbate concentrations, to determine the optimal conditions for the adsorption systems. The same sorbate volume (10 ml), and the same dosage (0.3g) of biosorbent were used for both adsorption processes. Linear analysis was used to compare the best-fitting isotherms. Langmuir, Freundlich, and Dubinin-Radushkevich models were tested. The highest coefficient of determination values (R2) for both iron (II) and Methylene blue was obtained from the Langmuir isotherm as 0.9266 and 0.9572, respectively, compared to values from the other isotherms tested – indicative of Langmuir isotherm’s superior fit. Estimated values of ‘separation factor’, KR, for Methylene blue (0.29457), however, was lower than that of iron (II) (0.42141) - an indication that the sorbent treats methylene blue better than iron (II), though both processes are feasible.